2021
DOI: 10.3390/ma14081878
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanism and Control Method of Residual Stress Profile by Laser Shock Peening in Thin Titanium Alloy Component

Abstract: In the laser shock peening process of titanium alloy thin blades, a shock wave will be repeatedly reflected and coupled in the blades, resulting in the failure of the formation of a gradient residual compressive stress layer, which is the key to improve fatigue performance and resist foreign object impact. This paper takes TC17 titanium alloy sheet as the research object to reveal the influence mechanism on residual stress-strain profile of shock wave reflection-coupling by shock wave propagation and key posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Most of these finite element simulations use a two-step analysis method of “dynamic explicit analysis + static implicit analysis” [ 28 ], which requires a lot of computational resources and is cumbersome when analyzing large models and multi-point impact problems. Scholars have proposed a continuous dynamic display analysis method [ 29 , 30 ]. This method uses CIN3D8 infinite elements as reflection-free boundaries to build a local model, which avoids the effects caused by the repeated transmission of stress waves inside the material and shortens the computational time.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these finite element simulations use a two-step analysis method of “dynamic explicit analysis + static implicit analysis” [ 28 ], which requires a lot of computational resources and is cumbersome when analyzing large models and multi-point impact problems. Scholars have proposed a continuous dynamic display analysis method [ 29 , 30 ]. This method uses CIN3D8 infinite elements as reflection-free boundaries to build a local model, which avoids the effects caused by the repeated transmission of stress waves inside the material and shortens the computational time.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical analysis showed that LSP suppresses an occurrence of tensile stress in the notch of the airfoil after the impact. Nie et al [11] developed a model with dynamic explicit and static implicit steps in the Abaqus software to study reflection and coupling of the shock wave induced by laser shots in a thin TC17 titanium alloy blade profile. It was shown that the transverse plastic strain induced by the first compression wave gradually decreases due to the action of the subsequent reflected tensile wave and the residual tensile stress is formed.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al [ 22 ] developed a three-dimensional semi-infinite finite element model to investigate the generation and propagation of the laser shock wave in Al2024 generated by the laser-induced plasma pressure, and the prediction results were verified by the PVDF measurements. Nie et al [ 23 ] developed two finite element models with thicknesses of 5 mm and 1 mm, and the bottom of the 5 mm-thickness target model was added the infinite elements to eliminate the affection of the laser plasma-induced shock wave reflection. Compared with the infinite thickness model, the propagation law of the LSP-induced shock wave and the dynamic response of material were analyzed, and the simulation results show that the reflection of the LSP-induced shock wave has an important impact on the LSP-induced residual stresses in the thin (sheet) model.…”
Section: Introductionmentioning
confidence: 99%